Dampak Penerapan Good Corporate Governance dan Corporate Social Responsibility terhadap Nilai Perusahaan - Wijaya, Sugianto; Suhartini, Dwi (Jurnal Etnik: Ekonomi-Teknik, 2023)
The value of the company is very directly related to the sustainability of the company in the future where one of the goals of the establishment of a company is to be able to stand up and continue to operate continuously in carrying out business operations the company has to obtain optimal profits. research is to examine the influence of Good Corporate Governance and Corporate Social Responsibility on company value. Determination of the sample was carried out using a purposive sampling method with the number of samples obtained were 26 companies listed on the IDX. The data was analyzed using descriptive analysis and multiple regression analysis. Companies in the food and beverage sector are strongly supported by the implementation of GCG and CSR. The results obtained from testing the hypothesis include, Good Corporate Governance has a positive impact on company value, Corporate Social Responsibility has a positive impact on company value. Good Corporate Governance has a significant positive effect on firm value and Corporate Social Responsibility has a significant positive effect on firm value.